Anti-Inflammatory Activity in the Low Molecular Weight Fraction of Commercial Human Serum Albumin (LMWF5A). Issue 1 (2nd January 2016) - Thomas, Gregory W.; Rael, Leonard T.; Mains, Charles W.; Slone, Denetta; Carrick, Matthew M.; Bar-Or, Raphael; Bar-Or, David
Abstract : The innate immune system is increasingly being recognized as a critical component in osteoarthritis (OA) pathophysiology. An ex vivo immunoassay utilizing human peripheral blood mononuclear cells (PBMC) was developed in order to assess the OA anti-inflammatory properties of the low molecular weight fraction (<5 kDa) of commercial human serum albumin (LMWF5A). PBMC from various donors were pre-incubated with LMWF5A before LPS stimulation. TNFα release was measured by ELISA in supernatants after an overnight incubation. A ≥ 30% decrease in TNFα release was observed. This anti-inflammatory effect is potentially useful in assessing potency of LMWF5A for the treatment of OA.